Conflict and Human Security in Africa - Kumssa, A. author. aut Link
XIII, 209 p. 3 illus.
Keywords: This edited volume looks at human security and conflict in northern Kenya and nearby areas within Sudan, Somalia, Ethiopia, and Uganda. It spells out the precise meaning and nuances of human security in today's global economy and examines the causes and effects of conflict in the region within the context of human security.